Coupled hydro-mechanical analysis of compacted bentonite behaviour during hydration. (December 2021) - Bosch, Jose A.; Ferrari, Alessio; Laloui, Lyesse
Abstract: This study analyses the response of compacted bentonites upon hydration based on a coupled hydro-mechanical elasto-plastic framework. As an alternative to multi-porosity interpretation, the framework was selected based on the experimental evidence of adsorbed water behaviour in bentonites and the volumetric response at saturated states, apparently independent of its initial state. Based on these premises, a water retention model was formulated using an explicit distinction between adsorbed water and free water, enabling the postulation of the water properties and behaviour depending on its state. In order to effectively account for the transition between unsaturated to saturated state, that can occur in a wide range of suctions, the stress–strain constitutive equations are written in terms of an effective stress and degree of saturation framework. The mathematical formulation was implemented in a finite element code and used to simulate and interpret the behaviour of MX-80 bentonite compacted in different forms during hydration for several stress paths, including loading and unloading cycles after saturation. A good agreement of the model with experimental results was obtained using a consistent set of parameters describing the saturated state behaviour. The typical non-linear swelling pressure development was interpreted through the two-way coupling between the water retention behaviour and elasto-plastic compressibility. The possible high suctions at saturated states explain the swelling potential after full hydration. Overall, this study offers new perspectives on the role of hydro-mechanical interactions in bentonite behaviour upon hydration.